Catalytic Liquid-Phase Oxidation of Phenolic Compounds Using Ceria-Zirconia Based Catalysts - Nunotani, Naoyoshi; Supandi, Abdul Rohman; Choi, Pil-Gyu; Imanaka, Nobuhito (Frontiers in Chemistry, 2018)
Catalytic liquid-phase oxidation using a catalyst and oxygen gas (Catalytic wet air oxidation; CWAO) is one of the most promising technology to remove hazardous organic compounds in wastewater. Up to now, various heterogeneous catalysts have been reported for phenolic compounds decomposition. The CeO2-ZrO2 based catalysts have been recently studied, because CeO2-ZrO2 works as a promoter which supplies active oxygen species from inside the lattice to the active sites. Since it is difficult to dissolve oxygen gas into water, the use of the promoter is effective for realizing the high catalytic activity at moderate conditions. Also, CeO2-ZrO2 shows high resistance for the metal leaching during the catalytic reaction in the liquid-phase. This article reviews the studies of the catalytic liquid-phase oxidation of phenolic compounds using CeO2-ZrO2 based catalysts.